2023
DOI: 10.1177/19417381231155120
|View full text |Cite
|
Sign up to set email alerts
|

Female Athletes With Better Psychological Readiness Are at Higher Risk for Second ACL Injury After Primary ACL Reconstruction

Abstract: Background: Approximately 1 in 4 athletes returning to sports will sustain a second anterior cruciate ligament (ACL) injury. Psychological factors related to kinesiophobia, confidence, and psychological readiness are associated with second ACL injury; however, the evidence is conflicting. Hypothesis: Athletes who sustain a second ACL injury (ie, graft rupture or contralateral ACL rupture) within 2 years of ACL reconstruction (ACLR) would have greater kinesiophobia, less confidence, and lower psychological read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…These results suggest that 6 months after reconstruction, increasing the ability to run and SLH distances in both the anterior and lateral directions will lead to improved results in risk appraisals. On the other hand, a recent study in female patients 7 months after reconstruction reported that higher Risk Appraisal scores were associated with a second injury [ 10 ]. Younger age was associated with higher Risk Appraisal score [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that 6 months after reconstruction, increasing the ability to run and SLH distances in both the anterior and lateral directions will lead to improved results in risk appraisals. On the other hand, a recent study in female patients 7 months after reconstruction reported that higher Risk Appraisal scores were associated with a second injury [ 10 ]. Younger age was associated with higher Risk Appraisal score [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ability to interpret the contribution of the involved limb variable to the overall ACL‐RSI value remains limited. Subcategory scores are affected by age and gender, so these must be taken into account when generalizing the findings [ 10 , 34 ]. In addition, the focus on hamstring tendon reconstruction limits the generalizability of findings to broader populations and different types of reconstructions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Contrarily, another study with a smaller sample size has also demonstrated that females with higher ACL-RSI scores were more likely to have a second ACL injury. 35 Thus, with the discrepancy of ACL-RSI scores with re-injury, this study was uniquely designed to differentiate objective MU characteristics of thigh musculature between those with disparate ACL-RSI scores (RSI-high and RSI-low) at 6 months and 12 months post-injury and healthy CTRLs. 31 36 This study aimed to determine the relationship of a subjective psychological readiness metric to RTS to objective measures of bilateral motor CTRL.…”
Section: Open Accessmentioning
confidence: 99%